Determinants of mobility ownership in Switzerland: changes between 2000 and 2010 - Kowald, Matthias; Barbara, Kieser; Mathys, Nicole; Justen, Andreas (My University, 2016)
The future development in mobility resource ownership is of great interest as the individual mobility behavior has critical impacts on transport infrastructure, land use, energy consumption, and environmental issues, such as greenhouse gas emissions and local air pollutants. Analysis and forecasts of mobility resource ownership as needed for example in transport modelling or forecast studies, however, usually employ data of the latest national travel surveys available. Therefore, changes in mobility resource ownership over time are often ignored. Estimating logit-based decision models on the large scale Swiss national travel survey data for 2000 and 2010, the study identifies determinants of mobility resource ownership for the main mobility resources (driving licenses, car availability, general abonnement travel tickets, and half fare travel tickets), identifying also significant changes over time. The predictor variables comprise socio-economic and socio-demographic variables, spatial structure features, and mobility resource specific characteristics. Our results show that age, sex, income, the size of the community, and geographical region influence mobility resource ownership in both years, 2000 and 2010. Furthermore, car-based and public transport-based mobility resources are substitutes for each other. Between 2000 and 2010 a behavioral change is observed for selected sub-populations: In 2010 women and persons above 40 years old are more likely to own a driving license and have a car available than in 2000. In addition, the positive effect of income on driving license and car ownership becomes smaller over time. Finally the previously neglected variables, such as household structure, employment status and level of education are found to be significant in the explanation of mobility resource ownership.
Keywords: Mobility resourcesMobility resource ownershipNational travel surveyDecision modelLogit model